Predictors of contralateral prophylactic mastectomy in genetically high risk newly diagnosed breast cancer patients - Tynan, Mara; Peshkin, Beth N.; Isaacs, Claudine; Willey, Shawna; Valdimarsdottir, Heiddis B.; Nusbaum, Rachel; Hooker, Gillian; O’Neill, Suzanne C.; Jandorf, Lina; Kelly, Scott P.; Heinzmann, Jessica; Kelleher, Sarah; et al. (Breast cancer research and treatment, 2020)
Purpose Recent trends indicate increased use of contralateral prophylactic mastectomy (CPM) among newly diagnosed breast cancer patients, particularly those who test positive for a pathogenic variant in the BRCA1/2 genes. However, the rate of CPM among patients who test negative or choose not to be tested is surprisingly high. We aimed to identify patient predictors of CPM following breast cancer diagnosis among such patients. Methods As part of a randomized controlled trial of rapid genetic counseling and testing vs. usual care, breast cancer patients completed a baseline survey within 6 weeks of diagnosis and before definitive surgery. Analyses focused on patients who opted against testing ( n = 136) or who received negative BRCA 1/2 test results ( n = 149). We used multivariable logistic regression to assess the associations between sociodemographic, clinical- and patient-reported factors with use of CPM. Results Among patients who were untested or who received negative test results, having discussed CPM with one’s surgeon at the time of diagnosis predicted subsequent CPM. Patients who were not candidates for breast-conserving surgery and those with higher levels of cancer-specific intrusive thoughts were also more likely to obtain a CPM. Conclusion The strongest predictors of CPM in this population were objective clinical factors and discussion with providers. However, baseline psychosocial factors were also independently related to the receipt of CPM. Thus, although CPM decisions are largely guided by relevant clinical factors, it is important to attend to psychosocial factors when counseling newly diagnosed breast cancer patients about treatment options.